Developing Phonemic Awareness and Phonics Skills to Read and Write - Andorka, Maggie (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
Difficulty with fluent word recognition often originates from a weakness in phonological processing. Children should learn English language foundational skills during the beginning stages of learning to read. Phonemic awareness and phonics work together to help students decode and spell accurately. Instruction in phonemic awareness (awareness of the individual speech sounds in spoken syllables and the ability to consciously manipulate those sounds) and phonics (mapping of individual speech sounds to the letters representing them) teach struggling readers the essential elements of language required for reading and writing. This manuscript addresses how to connect phonemic awareness and phonics instruction, strategies on how to identify struggling readers, and best teaching practices to help students struggling with phonemic awareness and phonics.